2002
DOI: 10.1111/j.1574-695x.2002.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of binding ofHelicobacter pylorito the glycolipid receptors by probioticLactobacillus reuteri

Abstract: We examined the competition of binding of Lactobacillus reuteri and Helicobacter pylori to gangliotetraosylceramide (asialo-GM1) and sulfatide which are putative glycolipid receptor molecules of H. pylori, and identified a possible sulfatide-binding protein of the L. reuteri strain. Among nine L. reuteri strains, two (JCM1081 and TM105) were shown to bind to asialo-GM1 and sulfatide, and to inhibit binding of H. pylori to both glycolipids by a thin layer chromatogram-overlay assay using biotin-labeled bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(50 citation statements)
references
References 32 publications
0
42
0
2
Order By: Relevance
“…The production of antimicrobial substances, such as lactic and acetic acid, is one example of this type of environmental modification [98]. Some lactobacilli and bifidobacteria share carbohydrate-binding specificities with some enteropathogens [99,100], which makes it possible for the strains to compete with specific pathogens for the receptor sites on host cells [101]. In general, probiotic strains are able to inhibit the attachment of pathogenic bacteria by means of steric hindrance at enterocyte pathogen receptors [102].…”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%
“…The production of antimicrobial substances, such as lactic and acetic acid, is one example of this type of environmental modification [98]. Some lactobacilli and bifidobacteria share carbohydrate-binding specificities with some enteropathogens [99,100], which makes it possible for the strains to compete with specific pathogens for the receptor sites on host cells [101]. In general, probiotic strains are able to inhibit the attachment of pathogenic bacteria by means of steric hindrance at enterocyte pathogen receptors [102].…”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%
“…Lactobacilli and bifidobacteria have been shown to inhibit a broad range of pathogens including E. coli , Salmonella , Helicobacter pylori , Listeria monocytogenes , and Rotavirus [21,51,52,53,54,55,56,57]. It has been shown that some lactobacilli and bifidobacteria compete for binding to host cell receptors because they share the same carbohydrate-binding specificities with some enteropathogens [58,59,60]. Lactobacillus rhamnosus has been shown to inhibit the internalization of enterohemorrhagic E. coli (EHEC) [61].…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment of broiler chicken with a multi-species probiotic consisting of bacteria isolated from the chicken gut prevented their colonization by Campylobacter jejuni 121 . The beneficial effects of probiotics are, to some extent, due to competitive exclusion of pathogenic bacteria from host binding sites, 122 - 124 although this is challenging to demonstrate in vivo because of the complexity of the probiotics’ mechanisms of action. Over recent years, probiotics have been specifically engineered to mimic sugars on host receptors, thereby blocking the host cell binding of toxins released by pathogenic bacteria including ETEC, shiga toxin-producing E. coli (STEC) and V. cholerae 125 - 127 .…”
Section: Improving Efficacy By Exploiting Multivalencymentioning
confidence: 99%